Therapy for Severe Gestoses in Incomplete Pregnancy - T. V. Pavlova; V. A. Petrukhin; A. N. Semykin (Общая реаниматология)
Objective: to improve pregnancy outcomes in severe gestosis. Subjects and methods: Sixty-five women with incomplete pregnancy in presence of severe gestosis were examined and the status of 65 neonatal babies was evaluated in the early neonatal period. The women were allocated into 3 groups: 1) 19 pregnant women were urgently operated on for severe admission condition (preeclampsia); 2) 22 pregnant women received standard therapy for gestosis; 3) 24 had standard therapy for gestosis in combination with 6% solution of the hydroxyethyl starch Stabisol®. Results. During gestosis therapy, pregnancy prolongation was 4.5±1.2 bed/days in Group 2 and averaged 7.6±1.6 bed/days in Group 3. The rate of neonatal referral to an intensive care unit was 63.1, 50.0, and 37.5% in Groups 1, 2, and 3, respectively. Referral to a neonatal pathology unit at the second stage of nursing was required in 100, 77.2, and 62.5% in Groups 1, 2, and 3, respectively. Conclusion. The use of 6% solution of the hydroxyethyl starch Stabisol® in complex therapy for gestosis in incomplete pregnancy prolongs pregnancy, accelerates rehabilitation in puerperas, prevents respiratory distress syndrome in full measure, and improves the neonatal adaptation period and perinatal outcomes as a whole. Key words: severe gestosis, incomplete pregnancy, 6% solution of Stabisol®.